Experimental periodontitis induced hypoadiponectinemia by IRE1α-mediated endoplasmic reticulum stress in adipocytes - Qianqi Wu; Li Yan; Xiao Wu; Yiyan Chen; Leilei Ye; Yingtao Lv; Yuan Su (BMC Oral Health, 2023)
Abstract Backgroud Hypoadiponectinemia is the important cause of insulin resistance. Recent studies have shown that periodontitis is associated with hypoadiponectinemia. The purpose of this study was to investigate the effect of periodontitis-induced endoplasmic reticulum stress (ERS) in visceral adipocytes on hypoadiponectinemia. Methods Rat periodontitis models were established by local ligation with silk around the bilateral maxillary second molars. Porphyromonas gingivalis-lipopolysaccharid (P.g-LPS) was also used to stimulate the visceral adipocytes in vitro. The protein expression levels of glucose regulated protein 78 (GRP78), inositol-requiring protein 1α (IRE1α), protein kinase RNA-like ER kinase (PERK), activating transcription factor 6 (ATF6) and adiponectin were detected. IRE1α lentiviruses were transfected into visceral adipocytes in vitro, and an IRE1α inhibitor (KIRA6) was injected in epididymal adipose tissue of rats to detect and verify the effect of ERS on adiponectin expression in visceral adipocytes in vivo. Results Hypoadiponectinemia was observed in periodontitis rat, and the expression levels of ERS key proteins GRP78 and the phosphorylation levels of IRE1α (p-IRE1α)/IRE1α in visceral adipocytes were increased, while the expression levels of adiponectin protein were decreased. After KIRA6 injection into epididymal adipose tissue of rats with periodontitis, adiponectin levels in visceral adipocytes increased, and serum adiponectin levels recovered to a certain extent. The protein expression levels of GRP78 and p-IRE1α/IRE1α were increased and adiponectin protein expression was decreased in P.g-LPS-induced visceral adipocytes. Overexpression of IRE1α further inhibited adiponectin expression in P.g-LPS-stimulated visceral adipocytes, and conversely, IRE1α inhibition restored adiponectin expression. Conclusions Our findings suggest that periodontitis induces ERS in visceral adipocytes leading to hypoadiponectinemia. IRE1α is a key protein regulating adiponectin expression in visceral adipocytes.